Effectiveness of Islamic Corporate Governance Mechanisms in Preventing Fraud: A Study of Islamic Commercial Banks in Indonesia, 2014-2023 - Fadilah, Yulhita Nur; Nugraha, Nyata; Nurhayati, Ida (Faculty of Sharia and Law, UIN Syarif Hidayatullah Jakarta, 2024)
This study aims to analyze the influence of the Sharia Supervisory Board (SSB), Audit Committee (AUDIT), Board of Commissioners (BOARDSIZE), Independent Board of Commissioners (INBOARD), and External Audit Quality (AUDITQUALITY) on Preventing Fraud (FRAUD) at Islamic Commercial Banks in Indonesia for the 2014-2023 period. The population includes 13 Islamic Commercial Banks registered with the Financial Services Authority. Using purposive sampling, 7 banks were selected. This research uses secondary data. The data analysis model employs multiple linear regression with panel data and is processed using Eviews 13. The results show that SSB, AUDIT, BOARDSIZE, INBOARD, and AUDITQUALITY simultaneously significantly affect Preventing fraud. Partially, SSB, INBOARD, and AUDITQUALITY positively and significantly affect Preventing fraud, while AUDIT and BOARDSIZE have a negative and non-significant effect on Preventing fraud. Penelitian ini bertujuan menganalisis pengaruh Dewan Pengawas Syariah (DPS), Komite Audit (AUDIT), Dewan Komisaris (BOARDSIZE), Dewan Komisaris Independen (INBOARD), dan Kualitas Audit Eksternal (AUDITQUALITY) terhadap Pencegahan Fraud (FRAUD) pada Bank Umum Syariah di Indonesia periode 2014-2023. Populasi adalah 13 Bank Umum Syariah yang terdaftar di Otoritas Jasa Keuangan. Sebanyak 7 bank terpilih secara purposive sampling. Penelitian ini menggunakan data sekunder. Model analisis data adalah regresi linier berganda dengan data panel dan diolah menggunakan Eviews 13. Hasil penelitian menunjukkan bahwa DPS, AUDIT, BOARDSIZE, INBOARD, dan AUDITQUALITY secara simultan berpengaruh signifikan terhadap Pencegahan fraud. Secara parsial, DPS, INBOARD, dan AUDITQUALITY berpengaruh positif dan signifikan terhadap Pencegahan fraud, sedangkan AUDIT dan BOARDSIZE berpengaruh negatif dan tidak signifikan terhadap Pencegahan fraud.